We Carry Our Homes With Us : A Cuban American Memoir - Veiga, Marisella (Book collections on Project MUSE., 2016)
"A memoir by a Cuban American writer, exploring issues of identity, biculturalism, and life exiled from a beloved homeland. The author spent much of her childhood (1960-75) in Minnesota"--